Challenges and Perspectives of Women's Entrepreneurship - Goran, Lapčević; Zorana, Nikitović; Shaik Azahar, Shaik Hussain; Eugen, Popescu; Carmine, D’arconte (Faculty of Business Economics and Entrepreneurship, 8, Mitropolita Petra Street, Belgrade, Serbia, 2025)
The paper deals with contemporary trends, challenges, and perspectives of the development of women entrepreneurship in a global and national context. The starting assumption of the work is that women entrepreneurship today plays an important role not only in economic growth but also in the processes of social transformation and gender equality. Key theoretical approaches, obstacles faced by women entrepreneurs, as well as opportunities for their inclusion in innovation and digital sectors, are analyzed. The method of analyzing secondary sources and a comparative approach that connects global and local trends was used. The results indicate that women still have difficult access to finance, the market, and support networks, but also that the situation is gradually changing through the growth of digital entrepreneurship, the development of mentoring programs, and institutional initiatives. Serbia follows most European trends, with the need for further strengthening of the financial and educational support system. It is concluded that women entrepreneurship has the potential to become one of the key pillars of sustainable development, provided that long-term and coordinated institutional support is provided.